2019
DOI: 10.1111/codi.14591
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal trainees in the UK struggle to meet JAG certification standards in colonoscopy by the end of their training

Abstract: Aim Colonoscopy certification in the UK is taken in two parts – provisional and full – mandating lifetime procedure counts of 200 or 300, respectively. The aim of this study was to determine the number of procedures performed by colorectal trainees by the end of training compared with their gastroenterology peers and to determine the factors associated with achieving the 300‐procedure target for full certification. Method Dates of entry onto the specialist register were obtained from the General Medical Counci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…This echoes previous studies that highlight the lack of accessible training for surgical trainees 15 and differences in list accessibility between trainee types, 16 which ultimately may have an impact on competency acquisition. 17 Cumulatively, this perhaps signifies a change in how training occurs. We may see this amplified with the advent of ‘Shape of Training’, which will shorten the effective training time for endoscopy within training programmes.…”
Section: Discussionmentioning
confidence: 99%
“…This echoes previous studies that highlight the lack of accessible training for surgical trainees 15 and differences in list accessibility between trainee types, 16 which ultimately may have an impact on competency acquisition. 17 Cumulatively, this perhaps signifies a change in how training occurs. We may see this amplified with the advent of ‘Shape of Training’, which will shorten the effective training time for endoscopy within training programmes.…”
Section: Discussionmentioning
confidence: 99%
“…indicating the Joint Committee on Surgical Training's commitment to colonoscopy training. However, several studies have reported a marked deficiency in colonoscopy training opportunities and accreditation for surgical trainees compared with gastroenterology trainees [2][3][4]. These challenges have been dramatically accentuated by the COVID-19 pandemic, reflecting a wider detrimental impact on endoscopy training across the world [5] The Joint Advisory Group on Endoscopy (JAG) has done much to improve the quality of colonoscopy in the UK in the past 20 years.…”
mentioning
confidence: 99%
“…Meanwhile, the new UK General Surgical curriculum now includes an indicative requirement of 200 diagnostic colonoscopies for surgical trainees who have declared a colorectal subspecialty interest (hereafter termed ‘colorectal trainees’), indicating the Joint Committee on Surgical Training’s commitment to colonoscopy training. However, several studies have reported a marked deficiency in colonoscopy training opportunities and accreditation for surgical trainees compared with gastroenterology trainees [2–4]. These challenges have been dramatically accentuated by the COVID‐19 pandemic, reflecting a wider detrimental impact on endoscopy training across the world [5] highlighting the urgent need for a more robust and equitable colonoscopy training programme in the UK.…”
mentioning
confidence: 99%
“…A further publication highlights this baseline deficiency in endoscopic training among colorectal trainees, with only 19% achieving 300 colonoscopies for full certification in 2017. 4 As many units are well under way in planning their return to endoscopy service delivery, it is unlikely that training will resume in the same capacity as it did beforehand. How long this is likely to be the case as yet remains unknown.…”
mentioning
confidence: 99%
“…A further publication highlights this baseline deficiency in endoscopic training among colorectal trainees, with only 19% achieving 300 colonoscopies for full certification in 2017. 4 …”
mentioning
confidence: 99%